(untitled) (Global Journal of Human-Social Science, 2023)
This article aims from the approach of the Cycle of Policies by Stephen J Ball and collaborators to present an analysis of the creation of the Accessibility and Inclusion Core NAI in a Brazilian federal university The contact with this particular experience makes it clear that there is undoubtedly progress but at the same time demonstrates the existence of a set of problems that prevented and or prevent the structuring of an effectively accessible and inclusive university Some of these issues were discussed in this work although others just highlighted deserve the attention of new research Whatever we believe that this initial reflection is justified and relevant because it helps to make visible some of the most important aspects of the debate regarding the inclusion of students with disabilities in Brazilian higher education